2002
DOI: 10.1124/jpet.301.2.418
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Functional Comparisons of Two Types of Tumor Necrosis Factor Antagonists

Abstract: Two tumor necrosis factor (TNF) antagonists infliximab (a chimeric monoclonal antibody) and etanercept (a p75 TNF receptor/Fc fusion protein) have been approved for treatment of rheumatoid arthritis. However, these agents have shown differ-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
444
3
19

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 606 publications
(491 citation statements)
references
References 36 publications
15
444
3
19
Order By: Relevance
“…Infliximab, by virtue of being IgGI antibodies, can activate complement and bind Fc receptor and it also can bind both monomeric and trimeric solTNF and tmTNF, whereas etanercept only binds TNF trimers and interacts with tmTNF with reduced avidity, compared with that of infliximab [82,[110][111][112].…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…Infliximab, by virtue of being IgGI antibodies, can activate complement and bind Fc receptor and it also can bind both monomeric and trimeric solTNF and tmTNF, whereas etanercept only binds TNF trimers and interacts with tmTNF with reduced avidity, compared with that of infliximab [82,[110][111][112].…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…Several of these studies have been performed using cell lines into which a gene encoding non-cleavable mTNF has been transfected. As discussed later in the next subsection, investigators have found differences in various anti-TNF agents in their ability to bind tmTNF [16]. Newer data suggest that the cross-linking of anti-TNF Ab on the cell is responsible for its reverse intracellular signaling, inhibiting the production of inflammatory cytokines, inducing apoptosis, and causing growth arrest.…”
Section: Intracellular Signaling Mediated By Anti-tnfα Agentsmentioning
confidence: 99%
“…At first the gene encoding tmTNF was transfected as a deletion mutant, but more recently, Harashima et al [68] developed a method of transfecting cells with a tmTNF rendered non-cleavable by site-directed mutagenesis. Using these methods, investigators assessed the number of anti-TNF molecules that can bind tmTNF either by flow cytometry or by radioassay [16].…”
Section: Limiting Factors Contributing To Disease Restriction In Thermentioning
confidence: 99%
See 2 more Smart Citations